2005
DOI: 10.1111/j.1365-246x.2005.02632.x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetism and40Ar/39Ar geochronology of mafic dykes from the eastern Bushveld Complex (South Africa)

Abstract: S U M M A R YWe report palaeomagnetic and 40 Ar/ 39 Ar age data for dykes that intrude the ∼2 Ga eastern Bushveld Igneous Complex (BIC). The dykes were previously assumed to be of Karroo age (Jurassic ∼ 180 Ma) based on their NE-SW orientation. Palaeomagnetic data (pole position 8.7 • N, 22 • E; dp/dm = 18/20.6 • ), however, clearly demonstrate that these dykes are Precambrian in age, either ∼1.9 Ga and close to the Early Proterozoic Bushveld age, or 1649 ± 10 Ma based on 40 Ar/ 39 Ar plagioclase laser fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…1). Paleoproterozoic magnetizations that pass reversal and baked-contact tests were reported for the BHDS (Letts et al, 2005(Letts et al, , 2011Lubnina et al, 2010) and are confirmed by combined U-Pb geochronology, geochemistry, and paleomagnetic data sets (Olsson et al, 2016;Wabo et al, 2019). Baddeleyite U-Pb crystallization ages of 12 dikes range between ca.…”
Section: The Black Hills Dike Swarmsupporting
confidence: 57%
“…1). Paleoproterozoic magnetizations that pass reversal and baked-contact tests were reported for the BHDS (Letts et al, 2005(Letts et al, , 2011Lubnina et al, 2010) and are confirmed by combined U-Pb geochronology, geochemistry, and paleomagnetic data sets (Olsson et al, 2016;Wabo et al, 2019). Baddeleyite U-Pb crystallization ages of 12 dikes range between ca.…”
Section: The Black Hills Dike Swarmsupporting
confidence: 57%
“…Recent paleomagnetic and magnetostratigraphic results dated to different time intervals of the Late Archean and of the Proterozoic also provided positive reversal tests, which again contradict the persistent or even the temporary occurrence of an asymmetrical geomagnetic field during this period. Among those studies, there are the data obtained from the ∼2.7 Ga flood basalts in the Pilbara craton (Western Australia) [ Strik et al , 2003], from the ∼2.0–1.6 Ga mafic dykes of the eastern Bushveld Complex (South Africa) [ Letts et al , 2005], from red beds in the ∼1.8 Ga Shoksha Formation (Russia) [ Pisarevsky and Sokolov , 2001], from the ∼1.4 Ga Belt‐Purcell Supergroup (North America) [ Elston et al , 2002], from the ∼1.1 Ga Umkondo dolerites in the Kalahari craton (southern Africa) [ Gose et al , 2006] and from the ∼0.8 Ga Aksu dyke swarm (Tarim basin) [ Chen et al , 2004]. We further note that positive reversal tests were also obtained from eastern Canadian formations and carbonatite complexes coeval with the ∼1.1 Ga Keweenawan lava flows [e.g., Costanzo‐Alvarez et al , 1993; Symons , 1994], which argues against a regional consistency of the asymmetrical geomagnetic reversals found in the Keweenawan lavas.…”
Section: Discussionmentioning
confidence: 99%
“…The dykes that produce negative anomalies are remanently magnetized (Letts et al. ). Figure (a) shows the original aeromagnetic data, whereas Fig.…”
Section: Mitigating the Amplitude Effectmentioning
confidence: 99%